FSH binding capability of gonadotrophin responsive follicles and probable role of LH on their release - SHARMA, G TARU; MAJUMDAR, A C (The Indian Journal of Animal Sciences, 2014)
Follicular fluid (FF) was collected f)’om the isolated large (>5 mm diameter) and medium (3-5 mm diameter) size gonadotrophin dependent forticles of early and late luteal phase of goat ovaries of abattoir origin for FSH ELISA to know the pattern and efficiency of FSH binding, its release from follicles under the influence of LH, and to assess the probahle role ofLH in an in vitro culture model. Nonatrectic, well voscularised follicles were cultured in TCM-199 having 5 ug FSH/ml for 30 min at 5% CO2, 95% RH and 38Â°C. After FSH incubation they were made free of unbound FSH and cultured with 741U LH/ml in TCM-199 with 10% EGS for 4,8,12 and 16 hr in 1 ml culture fluid. Follicles of control group were cultured in a similar fashion but without LH. After culture follicles were subjected to immunohistochemistry (IHC) and FSH waS estimated in the culture fluid. Higher FSH levels in the FF of both types of follicles were observed during late luteal phase compared to the early luteal phase. Treatment of the follicles with FSH increased FSH binding in the FF and showed the presence of free receptors in FE Medium sized follicles showed higher levels of FSH in culture fluid of LH treated group after 4hr of culture in comparison to large follicles. Maximum FSH concentration was observed at 8hr of culture in culture fluid with a decrease at 12 and 16hr. Control group had lower FSH levels compared to the LH treated group. At Ohr FSH was mainly localized in the FF and it decreased at 4hr. At 8hr it was mainly in the granulosa cells (GC) which further intensified in the GC at 12 and 16hr as compared to the FF. It may be concluded that the developing antral follicles synthesize FSH receptors that percolate in the FF and store FSH. On progesterone drop, FSH receptor complex of FF breakdown, releasing FSH, wh ich goes out of the follicles and binds to the GC surface, probably due to more number of receptors on GC at progesterone fall. This enhances estradiol and progesterone synthesis from GC similar to that of proestrus. Hence proestrus rise of circulating FSH, ifnot total then partly contributed by follicular FSH.